Coaching the double knee bend - Brewer, C.; Stone, M. (2008)
Introduction The correlation between maximal strength (the ability to produce maximal force) and power production is well documented (Schmidtbleicher, 1992; Stone 2002). Power (work/ time, or force x velocity) is a pre-requisite physical characteristic underpinning many aspects of sporting performance (acceleration, directional change, jumping actions and sports-specific skills: Hoff et al, 2001; Newton et al., 1997, Wisloff et al., 2004). The extant literature demonstrates that weight lifting movements (Snatch & Clean, and associated derivates of weightlifting [the practice of these movements in a sports context; Stone, Pierce, Sands & Stone, 2005]) may be superior training modalities for the development of Power (Stone, 2000; Tricoli et al., 2005).